Comparative study on methyl orange removal by growing cells and washed cell suspensions of Lactobacillus casei TISTR 1500 - Phisit Seesuriyachan (2018)
Lactobacillus casei TISTR 1500 possesses cytoplasmic azoreductase, and converts methyl orange to N,N-dimethyl-p-phenylenediamine and 4-aminobenzenesulfonic acid. In culture growth, the strain completely degraded methyl orange at 200 mg/l, even though the pH value was lower than 4. The decolorization was inhibited in the growing culture with 800 mg of the dye/l after incubation for 12 h. The percentage of decolorization and specific decolorization rate with 400 and 800 mg/l were 66 and 15%, and 14.2, and 8.7 mg/gCell/h, respectively. Additionally, a growing culture is more tolerant to a high initial dye concentration than when using washed cell suspensions supplied with only sucrose. Moreover, incubation of a low cell density in 600 μM of Na+and 20 mM of sucrose increased the specific decolorization rate from 2.34 mg/gCell/h (without Na+) to 4.32 mg/gCell/h. However, Na+had no effect on the enhancement of azoreductase activity in the reaction mixture. © 2009 Springer Science+Business Media B.V.